(untitled) (Al-Academy, 2016)
Represents the narrative and drama important sources in the serial drama television structure, and the advent of modern narrative techniques within the dramatic structure of the series of television directorial and processors that hired them, form a quantum leap in the level of the emergence of distinct forms of dramatic rely on narrative techniques according to the harmonic fabric is in control of making the form of art. dramatic and running events, but in order to discharge the need to adhere to the basics of drama and adapted within the mediator television capabilities, and narrative to make forms of television series to Atantzm in drift fixed because of the nature of governing structure formalism, this does not mean the existence of forms of dramatic irregular elements on the contrary, organized the elements according to building dramatic textured, and this is the narrative and drama of the most important sources in the construction of the structure of the television series